Maximal isometric handgrip strength in judo athletes from different age groups - Franchini, E.; Schwartz, J.; Takito. M. Y. (Sport Sciences for Health, 2020)
Purpose: This study aimed to compare the maximal isometric handgrip strength of 546 male judo athletes from different age groups (Cadet = 58; Junior = 118; Senior = 220; 30-39 years = 108; 40-49 years = 31; 51-59 years = 16).